2016
DOI: 10.3389/fcimb.2016.00145
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the NADH:NAD+ Homeostasis for Understanding the Metabolic Response of Mycobacterium to Physiologically Relevant Stresses

Abstract: The NADH:NAD+ ratio is the primary indicator of the metabolic state of bacteria. NAD(H) homeostasis is critical for Mycobacterium tuberculosis (Mtb) survival and is thus considered an important drug target, but the spatio-temporal measurements of NAD(H) remain a challenge. Genetically encoded fluorescent biosensors of the NADH:NAD+ ratios were recently described, paving the way for investigations of the metabolic state of pathogens during infection. Here we have adapted the genetically encoded biosensor Peredo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 57 publications
6
44
0
Order By: Relevance
“…Given our observation that MetT affects eukaryotic mitochondrial ROS production, we reasoned MetT may also affect mycobacterial energetics. To visualise disruption of cellular respiration in M. marinum , we created a transgenic M. marinum Δesx1 strain carrying pMV762-Peredox-mCherry (Addgene 90217) to visualise build up of NADH:NAD ratio [25, 26]. Analysis of constitutive mCherry expression in a late log culture revealed a small but statistically significant decrease in bacteria number following 1 mM MetT treatment and a larger decrease following 5 mM MetT treatment that was correlated with CFU counts (Fig 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Given our observation that MetT affects eukaryotic mitochondrial ROS production, we reasoned MetT may also affect mycobacterial energetics. To visualise disruption of cellular respiration in M. marinum , we created a transgenic M. marinum Δesx1 strain carrying pMV762-Peredox-mCherry (Addgene 90217) to visualise build up of NADH:NAD ratio [25, 26]. Analysis of constitutive mCherry expression in a late log culture revealed a small but statistically significant decrease in bacteria number following 1 mM MetT treatment and a larger decrease following 5 mM MetT treatment that was correlated with CFU counts (Fig 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Rv0148 is a NAD oxidoreductase involved in the function of intermediary metabolism and respiration. The exposure of Δ0148 to components inhibiting ETC complexes I and II [27] revealed that Δ0148 responds to changes in the electron transport system, thus predicting its role in cell homeostasis. M. tuberculosis adapts to various stress conditions to survive as a successful pathogen inside the host [28].…”
Section: Discussionmentioning
confidence: 99%
“…To understand the role of oxidative and nitrogen stress in H 37 Rv, Δ0148 and CΔ0148, the strains were grown to mid-log phase in 7H9-OADC-T medium and exposed to various stress components such as electron transport chain (ETC) inhibitors, peroxides, sulphoxides, thiol stress with slight modification to the procedure by [27] and OD values were measured at 600 nm (OD600) for 4, 24 and 48 h time points. The graphs were plotted and significance was reported considering P < 0.01 and P < 0.001.…”
Section: Role Of Knockout Mutant During Oxidative Stressmentioning
confidence: 99%
“…[ 50 ] Isoniazid and pyrazinamide induce changes to the NADH/NAD + ratio of the mycobacterium. [ 77 ] Isoniazid and pyrazinamide affect host, as well as mycobacterial, nicotinamide metabolism. Counterintuitively, isoniazid (INH) treatment is a known cause of pellagra, a host niacin (Vitamin B3) deficiency, possibly through competition between INH and niacin.…”
Section: Human and Microbial Nicotinamide Synthesis Pathways Interactmentioning
confidence: 99%
“…[ 114 ] Other relevant strategies have included using inhibitors targeting mycobacterial tryptophan synthesis [ 40,115 ] or the mycobacterial NAD + synthesis or recycling pathways. [ 50,72,77 ]…”
Section: The Ido Pathway Presents Therapeutic Targetsmentioning
confidence: 99%